Effects of Influenza Vaccination in the United States During the 2017–2018 Influenza Season. (2nd February 2019) - Rolfes, Melissa A; Flannery, Brendan; Chung, Jessie R; O'Halloran, Alissa; Garg, Shikha; Belongia, Edward A; Gaglani, Manjusha; Zimmerman, Richard K; Jackson, Michael L; Monto, Arnold S; Alden, Nisha B; Anderson, Evan; et al.
Abstract: Background: The severity of the 2017–2018 influenza season in the United States was high, with influenza A(H3N2) viruses predominating. Here, we report influenza vaccine effectiveness (VE) and estimate the number of vaccine-prevented influenza-associated illnesses, medical visits, hospitalizations, and deaths for the 2017–2018 influenza season. Methods: We used national age-specific estimates of 2017–2018 influenza vaccine coverage and disease burden. We estimated VE against medically attended reverse-transcription polymerase chain reaction–confirmed influenza virus infection in the ambulatory setting using a test-negative design. We used a compartmental model to estimate numbers of influenza-associated outcomes prevented by vaccination. Results: The VE against outpatient, medically attended, laboratory-confirmed influenza was 38% (95% confidence interval [CI], 31%–43%), including 22% (95% CI, 12%–31%) against influenza A(H3N2), 62% (95% CI, 50%–71%) against influenza A(H1N1)pdm09, and 50% (95% CI, 41%–57%) against influenza B. We estimated that influenza vaccination prevented 7.1 million (95% CrI, 5.4 million–9.3 million) illnesses, 3.7 million (95% CrI, 2.8 million–4.9 million) medical visits, 109 000 (95% CrI, 39 000–231 000) hospitalizations, and 8000 (95% credible interval [CrI], 1100–21 000) deaths. Vaccination prevented 10% of expected hospitalizations overall and 41% among young children (6 months–4 years). Conclusions: Despite 38% VE, influenza vaccination reduced a substantial burden of influenza-associated illness, medical visits, hospitalizations, and deaths in the United States during the 2017–2018 season. Our results demonstrate the benefit of current influenza vaccination and the need for improved vaccines. Abstract : During the 2017–2018 influenza season, we estimate that influenza vaccination reduced the risk of medically attended influenza by 38% and prevented 7 million illnesses, 4 million medical visits, 109 000 hospitalizations, and 8000 deaths in the United States.